PHP : Zend for i5/OS - Mullen-Schultz, Gary L.; Anderson, Melissa; Kosturjak, Vlatko (IBM redbooks., 2007)
This IBM Redbooks publication will help you install, configure, and become productive with PHP on System i using Zend Core for i5/OS and Zend Platform for i5/OS. If you are evaluating PHP, this book will also help by providing background information and comparisons with other tools. Some of the topics addressed include: Emphasis has been placed on highlighting i5/OS-specific functions and features in this book rather than those generic to PHP on all platforms.